PASTORAL KONSELING DALAM MEMBANGUN SPIRITUALITAS MAHASISWA KRISTEN DI TENGAH TEKANAN AKADEMIK - Desi Herpina Tojaya; Melda Sukudago; Jufri Kendek (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
In the context of increasingly competitive higher education, students often face various emotional and psychological challenges that can disrupt their mental and spiritual well-being. The approach of pastoral counseling oflers holistic support that integrates modern psychological principles with Christian faith values. This study aims to examine the role of pastoral counseling in building the spirituality of Christian students amid academic pressure. Through a literature review, this research investigates the methods and techniques used in pastoral counseling to assist students in managing stress, discovering their faith identity, and deepening their relationship with God. The findings indicate that pastoral counseling can serve as an eflective means of enhancing the spiritual resilience of students, as well as providing them with the necessary tools to cope with academic pressures. Approaches involving prayer, spiritual reflection, and the reinforcement of Christian identity have proven helpful for students in finding meaning and purpose in life amid challenges. Additionally, involvement in church communities is highlighted as a crucial aspect of supporting the process of recovery and spiritual growth. This research underscores the necessity for collaboration between educational institutions and churches in developing comprehensive pastoral counseling services, so that Christian students can grow in a balanced manner in both academic and spiritual aspects.